2021
DOI: 10.1002/ehf2.13216
|View full text |Cite
|
Sign up to set email alerts
|

A clinical score for predicting left ventricular reverse remodelling in patients with dilated cardiomyopathy

Abstract: Aims Left ventricular reverse remodelling (LVRR) is a well-established predictor of a good prognosis in patients with dilated cardiomyopathy (DCM). The prediction of LVRR is important when developing a long-term treatment strategy. This study aimed to assess the clinical predictors of LVRR and establish a scoring system for predicting LVRR in patients with DCM that can be used at any institution. Methods and results We consecutively enrolled 131 patients with DCM and assessed the clinical predictors of LVRR. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…This score has better predictability for LVRR in patients with DCM compared with late gadolinium enhancement on cardiac magnetic resonance imaging or fibrosis severity according to EMB. 11 The present study showed the PAD/ AoD ratio still had significant predictability, even after adjusting for this clinical predictive score.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…This score has better predictability for LVRR in patients with DCM compared with late gadolinium enhancement on cardiac magnetic resonance imaging or fibrosis severity according to EMB. 11 The present study showed the PAD/ AoD ratio still had significant predictability, even after adjusting for this clinical predictive score.…”
Section: Discussionsupporting
confidence: 45%
“…9,12, 32 We also evaluated the clinical score for predicting LVRR (LVRR predictive score) in patients with DCM using 5 predictors: history of hypertension (1 point), no family history of DCM (2 points), symptom duration <90 days (1 point), LVEF >35% (2 points), and QRS duration <116 ms (1 point). 11 Cardiac events included a composite of hospitalization due to worsening HF, lethal arrhythmia (hospitalization for hemodynamically unstable sustained ventricular tachycardia or ventricular fibrillation), LVAD implantation, and cardiac death. We collected outcome data using medical records or via telephone calls to patients or their families.…”
Section: Definition Of Lvrr and Cardiac Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilated cardiomyopathy (DCM) is a heterogeneous disease, and it is challenging to predict whether left ventricular functional recovery (left ventricular reverse remodeling [LVRR]) can be achieved (1)(2)(3). LVRR is indicative of a good prognosis and is achieved in about 40% of patients with DCM through optimal medical therapies (OMTs) (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Limited information is available on factors predicting the improvement in left ventricular ejection fraction (LVEF) by implementing drug therapy in patients with HFrEF ( 6 , 7 ), and LVRR usually occurs within 1–2 years in patients who experience heart attacks ( 8 ). ICD implantation is recommended as the primary form of prevention in clinical guidelines only when the LVEF is re-evaluated to be 35% again in patients after at least 3–6 months of receiving optimal drug therapy ( 9 ). Therefore, if we can identify LVRR in combination with several common clinical diagnosis methods in patients with an EF of ≤35% (HFrEF) at first diagnosis, this will aid in determining whether ICD implantation should be performed to prevent sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%